Coupling coordination mechanism of higher education and industrial economy: evidence from higher education institutions in Chongqing, China - Pengfei Guo; Hang Chen; Xinyun Hu (Humanities & Social Sciences Communications)
Abstract Based on the sample data of 63 higher education institutions in Chongqing from 2013 to 2022, this paper adopts the entropy value method and the coupling coordination degree evaluation model to measure the coupling coordination degree and coupling mechanism between higher education and industrial economy in Chongqing. The results of the study found that: (1) the level of higher education in Chongqing shows a trend of rapid growth followed by basic stability and slight decline during the sample period, with the public undergraduate > the public specialized > the private undergraduate > the private specialized, and the central urban area > the new area of the city proper > the two clusters. Meanwhile, the level of industrial economy and its three subsystems in Chongqing also showed an upward trend, in which industrial efficiency > industrial scale > industrial structure. (2) The coupling coordination degree between higher education and industrial economy in Chongqing is at a medium level, with a phenomenon of high constant high and low constant low. It is characterized by an olive-shaped structure with fewer areas at the two ends, more areas in the middle for the quantity distribution, and one area higher than two clusters for the geospatial distribution. (3) There is a mutual promoting effect between higher education and industrial economy in Chongqing. The development of higher education, industrial economy, industrial efficiency, industrial scale, and industrial structure can improve the coupling coordination degree. Except for the industrial scale, other variables have a positive moderating effect on the coupling coordination degree. In addition, the heterogeneity analysis shows that the positive effect of higher education on the coupling coordination degree is higher in private institutions, undergraduate institutions, two clusters, and new area of the city proper.